Aspects of emotional labor of public health nurses engaged in interpersonal support. Issue 2 (23rd September 2022) - Honda, Junko; Sasaki, Akiko; Tsuda, Shio; Matsuyama, Machiko; Morita, Kumiko
Abstract: Aim: Clarifying the emotional labor of public health nurses while providing interpersonal support. Design: Qualitative descriptive study conducted using content analysis to clarify the aspect of emotional labor of PHNs regarding interpersonal support. Methods: Individual semi‐structured interviews were conducted with 28 public health nurses employed by seven city governments in Japan. The data items obtained were categorized using deductive content analysis. Results: When attempting interpersonal support, PHNs showed the following aspects of emotional labor: (1) negative emotions towards residents and resident‐focused emotions; (2) emotional rules based on duty performance, emotional rules based on fairness, emotional rules based on intimacy; (3) adaptive emotional regulation, maladaptive emotional regulations and (4) emotional expressions based on friendliness, emotional expressions based on calmness. Conclusion: PHNs used adaptive emotional regulation in some cases and sometimes resorted to maladaptive forms. A system of support should be established to ensure the smooth and effective provision of interpersonal support.